Biomarkers and arrhythmia recurrence following radiofrequency ablation of atrial fibrillation. Issue 12 (December 2018) - Carballo, David; Noble, Stephane; Carballo, Sebastian; Stirnemann, Jérome; Muller, Hajo; Burri, Haran; Vuilleumier, Nicolas; Talajic, Mario; Tardif , Jean-Claude; Keller, Pierre-Frederic; Mach, Francois; Shah, Dipen
Objective: Atrial fibrillation (AF) is the most common cardiac arrhythmia, and radiofrequency catheter ablation of AF (RCAAF) has become increasingly popular. Cardiac stress and inflammation have been associated with AF. This study was performed to determine whether the pre- or post-AF ablation levels of high-sensitivity C-reactive protein (hs-CRP) and N-terminal pro–B-type natriuretic peptide (NT-proBNP) are predictive of AF recurrence. Methods: This multicenter prospective cohort study involved patients undergoing RCAAF in Switzerland and Canada. The primary endpoint was the recurrence of AF or atrial flutter at 6 months. Results: Of 202 patients, 195 completed follow-up (age, 57.5 ± 9 years; mean left ventricular ejection fraction, 62%; mean left atrial size, 19.4 cm 2 ). Patients with AF recurrence had larger atrial surfaces and longer total RCAAF times. Both the pre-ablation hs-CRP level and 1-day post-RCAAF NT-proBNP level were significantly associated with an increased risk of recurrence. Conclusions: The pre-ablation hs-CRP level and immediate post-ablation NT-proBNP level were markers for atrial arrhythmia recurrence after RCAAF. This confirms growing evidence of the role of inflammation in the pathogenesis of AF. These biomarkers appear to be promising stratification tools for selection and management of patients undergoing RCAAF.